Plasma membrane permeabilization to explain erythrosine B phototoxicity on in vitro breast cancer cell models - Bistaffa, Maria J. [UNESP]; Camacho, Sabrina A. [UNESP]; Melo, Carlos F.O.R. [UNESP]; Catharino, Rodrigo R.; Toledo, Karina A. [UNESP]; Aoki, Pedro H.B. [UNESP] (Elsevier, 2021)
Lipid oxidation is ubiquitous in cell life under oxygen and essential for photodynamic therapy (PDT) of carcinomas. However, the mechanisms underlying lipid oxidation in rather complex systems such as plasma membranes remain elusive. Herein, Langmuir monolayers were assembled with the lipid extract of glandular breast cancer (MCF7) cells and used to probe the molecular interactions allowing adsorption of the photosensitizer (PS) erythrosine B and subsequent photooxidation outcomes. Surface pressure (π) versus area (cm2/mL) isotherms of MCF7 lipid extract shifted to larger areas upon erythrosine incorporation, driven by secondary interactions that affected the orientation of the carbonyl groups and lipid chain organization. Light-irradiation increased the surface area of the MCF7 lipid extract monolayer containing erythrosine owing to the lipid hydroperoxidation, which may further undergo decomposition, resulting in the chain cleavage of phospholipids and membrane permeabilization. Incorporation of erythrosine by MCF7 cells induced slight toxic effects on in vitro assays, differently of the severe phototoxicity caused by light-irradiation, which significantly decreased cell viability by more than 75% at 2.5 × 10−6 mol/L of erythrosine incubated for 3 and 24 h, reaching nearly 90% at 48 h of incubation. The origin of the phototoxic effects is in the rupture of the plasma membrane shown by the frontal (FSC) and side (SSC) light scattering of flow cytometry. Consistent with hydroperoxide decomposition, membrane permeabilization was also confirmed by cleaved lipids detected in mass spectrometry and subsidizes the necrotic pathway of cell death.
Keywords: Erythrosine B; Glandular breast cancer (MCF7) cells; Langmuir films; Photodynamic therapy (PDT)